Alexithymia disrupts emotion regulation processes and is associated with greater negative affect and alcohol problems. Issue 12 (17th November 2021) - Linn, Braden K.; Zhao, Junru; Bradizza, Clara M.; Lucke, Joseph F.; Ruszczyk, Melanie U.; Stasiewicz, Paul R.
Abstract: Objective: Alexithymia is common among people who abuse alcohol, yet the mechanisms by which alexithymia exerts its influence remain unclear. This analysis tested a model whereby the three subscales of the Toronto Alexithymia Scale exert an indirect effect on alcohol problems through difficulties with emotion regulation and psychological distress. Method: Men and women ( n  = 141) seeking alcohol use disorder (AUD) treatment completed the Toronto Alexithymia Scale, the Difficulties with Emotion Regulation Scale, the Brief Symptom Inventory, the Short Inventory of Problems, and the Alcohol Dependence Scale. Results: The Difficulty Identifying Feelings subscale of the Toronto Alexithymia Scale was positively associated with alcohol problems through emotion dysregulation and psychological distress. The other two subscales, Difficulty Describing Feelings and Externally oriented Thinking, were not associated with any other variables. Conclusion: People with alexithymia may consume alcohol to help regulate undifferentiated states of emotional arousal. Given the prevalence of alexithymia among people who abuse alcohol, treatment supplements that enhance the identification of emotions are needed.